Etika Pendidikan Tentang Berbicara dan Diam Menurut Al-Mawardi dalam Kitab Adab Al-Dunya Wa Al-Din - Rahman, Abdur (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
Speaking is one thing that distinguishes humans and animals. Speaking goodmakaes humans more appreciated. Therefore, speaking good is so important thatthey do not make mistakes. In this instance, a book of Sufism, al-Dunya wa al-Din the work of al-Ma Wardi. Al-Ma Wardi, is used to discuss this matter. He isone of Muslim scholars who is expert in this field. He wrote in the book 'ethics ofspeech and silence'. In education it is generally better to be silent, because Godcreated humanswith two ears and one mouth. If you must talk, then you shouldpay attention to four conditions. First, the words must able to attract the audience,whether it is for the sake of benefit or to get rid of danger. Second, speaking shouldbe in proper place. Third, the words should be concise. And fourth, choosing theright vocabulary to speak. In addition, to beautify the words, someone could useamtha l.